IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE OF TPS BASED SAVI TO COMPLETE STUDENT LEARNING OUTCOME - iva septy wulandari; Muchlis Muchlis (Universitas Negeri Surabaya, 2020)
This study aims to describe the implementation, activities, learning outcomes, and student responses after the application of SAVI type TPS-based cooperative learning models of electrolyte and non-electrolyte solution materials. This study uses